Effects of Tolvaptan in patients with acute heart failure: a systematic review and meta-analysis - Chunbin Wang; Bo Xiong; Lin Cai (BMC Cardiovascular Disorders, 2017)
Abstract Background Acute heart failure, which requires urgent evaluation and treatment, is a leading cause for admission to the emergency department. The aim of this meta-analysis was to evaluate the effects of tolvaptan on acute heart failure and compare them with the effects of conventional therapy or placebo. Methods The electronic databases PubMed, EMBASE, and the Cochrane Controlled Trial registry were searched from their starting dates to October 24, 2016. Two authors independently read the trials and extracted related information from the included studies. We used fixed-effects or random-effects models to assess the overall combined risk estimates according to I2 statistics. Analysis to determine sensitivity and publication bias was conducted. Results Six randomised controlled trials from eight articles, with a total of 746 patients, were included for analysis. Compared with the control, tolvaptan reduced body weight in two days (WMD 1.35; 95% CI 0.75 to 1.96), elevated sodium level in two days (WMD 2.33; 95% CI 1.08 to 3.57) and five days (WMD 1.57; 95% CI 0.04 to 3.09), and ameliorated symptoms of dyspnoea (RR 0.82; 95% CI 0.71–0.95). However, tolvaptan did not improve long-term (RR 1.04; 95% CI 0.66–1.62) or short-term all-cause mortality (RR 0.89; 95% CI 0.45–1.76), incidence of clinical events (worsening heart failure, RR 0.75; 95% CI 0.50–1.12 and worsening renal function, RR 0.97; 95% CI 0.75–1.27), and length of hospital stay in patients (WMD 0.14; 95% CI -0.29 to 2.38) with acute heart failure. Conclusion Tolvaptan can decrease body weight, increase serum sodium level, and ameliorate some of the congestion symptoms in patients with acute heart failure, which may help avoid the overdose of loop diuretics, especially in patients with renal dysfunction.